PL.100 Time to Discharge Following Uncomplicated Elective or Emergency Caesarean Section: is Patient Motivation the Major Determining Factor?. (26th April 2013) - Rundle, S; Ash, J; Kay, T
Abstract : Anticipated increase in the rate of Caesarean birth following the publication of recent National Institute of Health and Clinical Excellence guidance 1 prompted investigation into the causes of delay in discharge from hospital following an uncomplicated elective or emergency Caesarean section. A retrospective audit of the patient health record at the Royal Devon and Exeter Hospital revealed that time to discharge appeared to be independent of parity, urgency of delivery (elective or emergency Caesarean section) or intended feeding method (breast of artificial feeding). In patients without medical or surgical complications following Caesarean delivery, it was expected that delay in medical and midwifery staff performing routine care needs would be responsible for any delay in discharge. Routine and measurable care needs, identified as being compulsory prior to discharge were: 1. Removal of the indwelling urinary catheter and successful trial without catheter (TWOC), 2. Documented confidence and competence at breast-feeding, for those choosing this method, 3. Ability to administer low molecular weight thromboprophylaxis independently of a midwife or health professional, and, 4. Ability to self-administer post-operative analgesia. On no identifiable occasion did unnecessary delay in the performance of these needs adversely affect time to discharge. These results suggest that in our unit patient motivation factors as well as individual expectation of the recovery period may be the biggest determinants of time to discharge following Caesarean section. Reference: National Institute for Health and Clinical Excellence. NICE clinical guideline 132, Caesarean Section: November 2011.